2016
DOI: 10.1128/genomea.01329-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence Analysis of Acute and Mild Strains of Classical Swine Fever Virus Subgenotype 3.2

Abstract: We report the complete genome sequences of two classical swine fever virus strains (JJ9811 and YI9908). Both belong to subgenotype 3.2. Strain JJ9811 causes mild symptoms and strain YI9908 causes acute symptoms. The sequences were 95.7% homologous at the nucleotide level and 95.6% homologous at the amino acid level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This lineage showed a genetic divergence compared to the remaining CSFV genotypes that ranged between 15.6% and 19.1% (Figure c). The CSFV strains JJ9811 and YI9908 have been previously classified as Genotype 3, Subgenotype 3.2 (Lim et al., ). However, this previous classification was based on the phylogenetic analysis using the segment of E2 comprising 190 nt (E2‐190 marker) (Lowings, Ibata, Needham, & Paton, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lineage showed a genetic divergence compared to the remaining CSFV genotypes that ranged between 15.6% and 19.1% (Figure c). The CSFV strains JJ9811 and YI9908 have been previously classified as Genotype 3, Subgenotype 3.2 (Lim et al., ). However, this previous classification was based on the phylogenetic analysis using the segment of E2 comprising 190 nt (E2‐190 marker) (Lowings, Ibata, Needham, & Paton, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, these isolates were reclassified as Subgenotype 1.4 when the phylogenetic analysis was accomplished using the E2‐complete gene marker that showed a genetic segregation between 9.8% and 15.8% to sequences of Subgenotype 1.2 (Postel et al., ). Thus, the use of the marker E2‐190 (Lowings et al., ) could have lead to a misclassification of the CSFV strains JJ9811 and YI9908 into the Subgenotype 3.2 (Lim et al., ). It is also relevant to consider that the lineage formed by the CSFV strains JJ9811 and YI9908 showed a genetic divergence of 16.6% with the CSFV strains belonging to the Genotype 3 (Figure b and c).…”
Section: Resultsmentioning
confidence: 99%
“…No information is available regarding the virulence of the strain isolated in the United Kingdom, which belongs to genotype 4. In the genotype 5 strains in South Korea, YI9908 (KT716271) showed acute CSF, while JJ9811 (KF669877) showed milder clinical signs of CSF in experimental conditions (Lim et al., 2016). The lack of information, especially about genotypes 4 and 5, necessitates further data collection and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, the mutations N 40 D and N 40 E on reacted HCLV-E2 could effectively abolish or diminish its reactivity with mAb 6B211, while mutation D 40 N on unreacted GD53-E2 could generate its reactivity with mAb 6B211 (Figure 4C). Meanwhile, mutations L 37 G, L 39 A, D 41 T, and D 42 L, but not D 36 G, Q 38 G, T 43 G, V 44 A, and K 45 G, at flanking sites of reacted HCLV-E2 also abolished or significantly diminished its reactivity with 6B211 (Figure 4C). These results showed that the critical aa motifs of mAbs 9A4H4-and 6B211-recognizing epitopes are 271 RXGP 274 and 37 LXLNDG 42 , respectively.…”
Section: Critical Aa Motifs Of the Epitopes Recognized By Anti-e2 Mabsmentioning
confidence: 97%
“…To further characterize the reactivity spectrum of the mAbs, E rns and E2 proteins of CSFV field isolates and vaccine strains of other sub-genotypes unavailable in our laboratory were respectively expressed in the above baculovirus system using synthesized gene fragments based on published sequences in GenBank [Figure S1 and Table S1 (7,17,(38)(39)(40)(41)(42)(43)(44)(45)]. The binding of anti-E rns and anti-E2 mAbs with recombinant E rns and E2 proteins was analyzed by Western blot as previously described (36,46).…”
Section: Identification Of Specificity and Reactivity Of Anti-e Rns A...mentioning
confidence: 99%